Shear behaviour of ultra-high performance concrete beams with openings. (September 2022) - Elsayed, Mahmoud; Badawy, Samah; Tayeh, Bassam A.; Elymany, Magdy; Salem, Mohamed; ElGawady, Mohamed
Abstract: An experimental investigation of the shear behaviour of Ultra-high performance concrete (UHPC) beams with web openings was conducted. Eight UHPC beams were experimentally cast and subjected to a four-point bending test. One beam, which was considered the control specimen, had no web openings, whereas the seven other beams contained openings. The studied parameters were steel fibre content, opening position, opening shape and reinforcement schemes around the web openings. Shear behaviour was evaluated on the basis of cracking patterns, load-deflection behaviour, ductility, initial stiffness, toughness and strain. Experimental results showed that increasing the volume fraction of steel fibres enhanced the shear strength, stiffness, toughness, ductility and strain in steel reinforcements. The presence of web openings in the shear region led to a decrease in the shear strength by 33.7%. The ultimate load of UHPC beams with openings has been evidently improved using reinforcement around the openings. An analytical verification was proposed to evaluate the experimental test results of UHPC beam by using design codes, different prediction equations and the empirical equation proposed herein. The proposed empirical equation showed an excellent agreement with available experimental data.